Sprowadź wyrażenia do najprostszej postaci:

a) – (2x – 7y + 5) + (– 3x – 4 + 7y) =  

 


b) (4a – 2b) – 6a – (7b – 8) =



c) 3a – (5b – 18) + 5a + 9 =  



d) 4 ∙ (–2 – 5x + 8y) =  



e) – 8 ∙ ( 5 – 6x + 2xy) – 10xy =



f) – 0,2 ∙ (-0,5x + 4y+ 6) =




Odpowiedź :

Odpowiedź:

a) -(2x-7y+5)+(-3x-4+7y)= -2x+7y-5+(-3)-4+7y=-2x+14y-12

b)(4a -2b)- 6a -(7b -8)=4a-2b -6a -7b+8= -2a-9b-8

c) 3a- ( 5b- 18) +5a +9= 3a - 5b+18 +5a+9=8a-5b+27

d) 4 * (-2- 5x+ 8y)= -8 -20x +32y

e) -8* ( 5- 6x +2xy)- 10xy= -40+48x-16xy-10xy=-30+48x-26xy

f)-